Bioethics teaching: evaluation of students through internet discussion forums - Rennó Junqueira, Cilene; Machado Tavares da Silva, Priscila; Rennó Junqueira, Simone; De Paula Ramos, Dalton Luiz (Acta Bioethica, 2012)
Bioethics learning has mainly being developed in classroom activities. Without pretending to substitute this classical face to face model, bioethics discipline, taught to first year students at day and night courses in Dentistry Department of Sao Paulo University, has been complemented by supervised visits to Department Clinics, as well as on line studies using Moodle platform. In this study students’ records of discussion forums in Moodle platform in 2008 were evaluated to verify their perception about the proposal of supervised visits to clinical practice during their learning process. 71 of 100 students who published comments in discussion forums accepted to participate in the study. This is a qualitative study carried out by thematic content analysis. Students’ perceptions about clinical practice allow professors to enhance their practice as pedagogical strategy for future classes and this may serve as model for other institutions.